INDONESIA Analisis Strategi Koperasi Pondok Pesantren Dengan Pendekatan Business Model Canvas dan Analisis SWOT (Studi Kasus KSPS BMT UGT Sidogiri Indonesia) - Royhan Syaputra; Achmad Firdaus (Mumtaz Publishing, 2024)
This study aims to determine the strategies and alternative strategies of KSPS BMT UGT Sidogiri using the BMC approach and SWOT Analysis. This research uses a qualitative descriptive approach with a Business Model Canvas approach and SWOT analysis at KSPS BMT UGT Sidogiri, Indonesia. The results of the study show that based on the SWOT Business Model Canvas analysis of KSPS BMT UGT Sidogiri Indonesia, KSPS BMT UGT Sidogiri had to add some segments, namely the customer/member segment, which increased to three, and the addition of new branches. Second, the value proposition adds to the ease of online access. Third, the channel segment adds to information technology. Fourth, maintaining relationships with members is very good through a direct approach, product value, and rewards. Fifth, the revenue stream segment adds new business units. Sixth, the main resources owned are very good, but it is necessary to improve human resource welfare and utilize alumni networks. Seventh, key activities need to include innovation and product development. Eighth, the main partnership needs to be supplemented by obtaining new partners, and the expansion of the cooperative business will further develop. Ninth, with the development of cooperatives, for business expansion, it is necessary to add costs for adding new branches and HR welfare costs. Thus, KSPS BMT UGT Sidogiri Indonesia must dare to expand new branches on the strength of the cooperative business model canvas and its opportunities (rapid growth). All strategies produced in this study are related to one another, so cooperation from all parties in the KSPS BMT UGT Sidogiri Indonesia is needed so that the nine business model canvasses can be run properly. If applied, the cooperative will be better.